In the Right Place at the Wrong Time: The Role of Firms and Luck in Young Workers' Careers - Wachter, Till von; Bender, Stefan (American Economic Review, 2006)
We exploit administrative data on young German workers and their employers to study the long-term effects of an early job loss. To account for non-random sorting of workers into firms with different turnover rates and for selective job mobility, we use changes over time in firm- and age-specific labor demand as an instrument for displacement. We find that wage losses of young job losers are initially 15% but fade to zero within five years. Only workers leaving very large establishments suffer persistent losses. A comparison of estimators implies that initial sorting, negative selection, and voluntary job mobility may have biased previous U.S. studies finding permanent effects of early displacements.